In the Light of Evolution: A Reevaluation of Conservation in the CO–FT Regulon and Its Role in Photoperiodic Regulation of Flowering Time - Ballerini, Evangeline S.; Kramer, Elena M. (Frontiers in Plant Science, 2011)
In order to maximize reproductive success, plants have evolved different strategies to control the critical developmental shift marked by the transition to flowering. As plants have adapted to diverse environments across the globe, these strategies have evolved to recognize and respond to local seasonal cues through the induction of specific downstream genetic pathways, thereby ensuring that the floral transition occurs in favorable conditions. Determining the genetic factors involved in controlling the floral transition in many species is key to understanding how this trait has evolved. Striking genetic discoveries in Arabidopsis thaliana (Arabidopsis) and Oryza sativa (rice) revealed that similar genes in both species control flowering in response to photoperiod, suggesting that this genetic module could be conserved between distantly related angiosperms. However, as we have gained a better understanding of the complex evolution of these genes and their functions in other species, another possibility must be considered: that the genetic module controlling flowering in response to photoperiod is the result of convergence rather than conservation. In this review, we show that while data clearly support a central role of FLOWERING LOCUS T (FT) homologs in floral promotion across a diverse group of angiosperms, there is little evidence for a conserved role of CONSTANS (CO) homologs in the regulation of these loci. In addition, although there is an element of conserved function for FT homologs, even this component has surprising complexity in its regulation and evolution.